ANALYSIS OF LABORATORY MANAGEMENT AND UTILIZATION IN SCIENCE LEARNING AT BANYUAJUH 2 ELEMENTARY SCHOOL - Basyar Salim; Rika Wulandari; Kusnaningsih Kusnaningsih (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Science learning does not require that students only understand the material in theory, but students must be able to learn the theory they have learned. One of the facilities for carrying out practicum activities is the laboratory. Laboratory facilities certainly have elements of laboratory management and utilization which make all laboratory activities more systematic so that laboratory use can run optimally. The purpose of this research is to find out the management and utilization of laboratories at Banyuajuh 2 Elementary School before the pandemic and after the Covid-19 pandemic. The research method used in this research is descriptive qualitative. The data collection technique used is interview. Based on the research results obtained, the Banyuajuh 2 Elementary School has a laboratory facility in which there are many laboratory tools that can be used in science learning. The school also has manuals or SOPs for laboratory management and use. During the Covid-19 pandemic, all students carried out courageous learning and carried out practical work independently at their respective homes